Clinical Outcome after Colonic Resection in Women with Endometriosis. (15th July 2015) - Klugsberger, Bettina; Shamiyeh, Andreas; Oppelt, Peter; Jabkowski, Christina; Schimetta, Wolfgang; Haas, Dietmar
Abstract : Background . In severe forms of endometriosis, the colon or rectum may be involved. This study evaluated the functional results and long-term outcome after laparoscopic colonic resection for endometriosis. Patients and Methods. Questionnaire survey with 24 women who had experienced typical symptoms, including pelvic pain, infertility, and endometriotic lesions in the bowel and undergone laparoscopic surgery, including low anterior resection, from 2009 to 2012, was conducted. Results. Information about the postoperative outcome was obtained from 22 women and was analyzed statistically. Twenty-one had undergone low anterior resection; one patient required a primary Hartmann procedure due to a rectovaginal fistula. The conversion rate was 4.5%. Major complications occurred in one patient, including an anastomotic leakage, and a Hartmann procedure was carried out subsequently in this patient. The symptoms of pain during defecation, pelvic pain, dyspareunia, dysmenorrhea, and hematochezia showed clear improvement one year after the operation and at the time of the questionnaire. Conclusion . Laparoscopic low anterior resection for deeply infiltrative endometriosis is technically demanding but feasible and safe, and it improves the clinical symptoms of endometriosis in the bowel.